Neurology in Canada: History of the Canadian Neurological Society - Murray, T. Jock (Lippincott Williams & Wilkins, 2013)
In the 19th and early 20th century, Canadian physicians interested in neurology focused on this area as part of their broader clinical practices. The most renowned was William Osler, often called Canada's first neurologist because one-third of his writing was devoted to neurology. Until the mid-20th century, most Canadian neurologists trained at the National Hospital, Queen Square, London, and in Paris. The majority returned to academic centers and after World War II every Canadian medical school and major center had consultant neurologists.